2022
DOI: 10.1093/ve/veac078
|View full text |Cite
|
Sign up to set email alerts
|

Lineage BA.2 dominated the Omicron SARS-CoV-2 epidemic wave in the Philippines

Abstract: The Omicron SARS-CoV-2 variant led to a dramatic global epidemic wave following detection in South Africa in November, 2021. The Omicron lineage BA.1 was dominant and responsible for most SARS-CoV-2 outbreaks in countries around the world during December 2021-January 2022, whilst other Omicron lineages including BA.2 accounted for the minority of global isolates. Here, we describe the Omicron wave in the Philippines by analysing genomic data. Our results identify the presence of both BA.1 and BA.2 lineages in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
3
2
0
Order By: Relevance
“…November 2021), respectively (Figure 5). The substitution rates of BA.1 and BA.2 were estimated to be 1.435 × 10 −3 (95% HPD = 1.021 × 10 −3 − 1.869 × 10 −3 ) substitution/site/year and 1.074 × 10 −3 (95% HPD = 6.444 × 10 −4 − 1.586 × 10 −3 ) substitution/site/year, respectively, which is in line with several previous studies that estimated the substitution rates of SARS-CoV-2 [9,[80][81][82]. In comparison to our dataset's tMRCA for the BA.1 sub-lineage, the estimated tMRCA of the South African BA.1 sub-lineage sequence was found to be early October 2021 (9 October 2021, 95% HPD 30 September-20 October 2021) [9].…”
Section: Bayesian Molecular Dating Analyses Of Omicron Vocsupporting
confidence: 92%
See 1 more Smart Citation
“…November 2021), respectively (Figure 5). The substitution rates of BA.1 and BA.2 were estimated to be 1.435 × 10 −3 (95% HPD = 1.021 × 10 −3 − 1.869 × 10 −3 ) substitution/site/year and 1.074 × 10 −3 (95% HPD = 6.444 × 10 −4 − 1.586 × 10 −3 ) substitution/site/year, respectively, which is in line with several previous studies that estimated the substitution rates of SARS-CoV-2 [9,[80][81][82]. In comparison to our dataset's tMRCA for the BA.1 sub-lineage, the estimated tMRCA of the South African BA.1 sub-lineage sequence was found to be early October 2021 (9 October 2021, 95% HPD 30 September-20 October 2021) [9].…”
Section: Bayesian Molecular Dating Analyses Of Omicron Vocsupporting
confidence: 92%
“…This discrepancy is likely due to differences in the dataset's geographical heterogeneity. The tMRCA estimate for the BA.2 sub-lineage is in perfect accord with other studies, such as the tMRCA of BA.2 sub-lineage on 6 November 2021 (95% HPD = 9 October 2021 to 29 November 2021) [26], and mid-November for the Philippines BA.2 lineage sequences (18 November 2021; 95 % HPD = 6-28 November 2021) [82]. Since the BA.1 and BA.2 sub-lineages exhibit different tMRCAs, which is in line with the more recent emergence of BA.2 as compared to BA.1, they are expected to bear sub-lineage specific mutational profiles, and it is possible that these two sub-lineages of Omicron VOC might have originated and evolved independently.…”
Section: Bayesian Molecular Dating Analyses Of Omicron Vocsupporting
confidence: 90%
“…This discrepancy is likely due to differences in dataset's geographical heterogeneity. The tMRCA estimate for the BA.2 sublineage is in perfect accord with other studies, such as the tMRCA of BA.2 sub-lineage on 6 November 2021 (95% HPD = 9 October 2021 to 29 November 2021) [19], and mid-November for Philippines BA.2 lineage sequences (18 November 2021; 95 % HPD = 6-28 November 2021) [75]. Because the BA.1 and BA.2 sub-lineages exhibit different tMRCA and have distinct mutational profiles, it is possible that these two sub-lineages of Omicron VOC might have originated and evolved independently.…”
Section: Bayesian Molecular Dating Analyses Of Omicron Vocsupporting
confidence: 90%
“… 7 In the Philippines, the Delta variant dominated COVID-19 cases in 2021 while the Omicron variant dominated in 2022. 8 9 Despite the numerous variants circulating in the country, genomic sequencing of COVID-19 variants remains limited and not part of routine case reporting of the Department of Health (DOH). 10 Regardless of this limitation, there are limited studies that identified the common risks attributed to COVID-19 infection in the local population, especially with unvaccinated pregnant women and their unborn.…”
Section: Introductionmentioning
confidence: 99%
“…Two years have passed since the pandemic started, with several variants emerging such as the Alpha, Beta, Delta and Omicron, that resulted in several surges that took the lives of millions 7. In the Philippines, the Delta variant dominated COVID-19 cases in 2021 while the Omicron variant dominated in 2022 8 9. Despite the numerous variants circulating in the country, genomic sequencing of COVID-19 variants remains limited and not part of routine case reporting of the Department of Health (DOH) 10.…”
Section: Introductionmentioning
confidence: 99%